2017
DOI: 10.3390/ijms18040768
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fluorinated Non-Peptidic Ghrelin Receptor Ligands for Potential Use in Molecular Imaging

Abstract: The ghrelin receptor (GhrR) is a widely investigated target in several diseases. However, the current knowledge of its role and distribution in the brain is limited. Recently, the small and non-peptidic compound (S)-6-(4-bromo-2-fluorophenoxy)-3-((1-isopropylpiperidin-3-yl)methyl)-2-methylpyrido[3,2-d]pyrimidin-4(3H)-one ((S)-9) has been described as a GhrR ligand with high binding affinity. Here, we describe the synthesis of fluorinated derivatives, the in vitro evaluation of their potency as partial agonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In vivo biodistribution studies showed relatively low levels of tracer uptake in the mouse brain for all 3 radioligands, likely due to their relatively high lipophilicities ( Another group seeking to generate compounds suitable for GHSR imaging in the brain reported a SAR study on fluorinated quinazolinone derivatives with low nanomolar affinities. 94 Substitution at the piperidine nitrogen is known to have an effect on binding to the receptor; therefore, the authors chose a known, high affinity, quinazolinone derivative as a starting point for SAR studies, compound 24. 95 Results from the study revealed that both enantiomers of the original lead candidate, (S)-24 and (R)-24, and a new derivative, (S)-25 had the strongest binding affinities (IC 50 ¼ 2.2 nM, 3.9 nM, and 2.7 nM, respectively).…”
Section: Molecular Imaging Agents Based On Small Moleculesmentioning
confidence: 99%
“…In vivo biodistribution studies showed relatively low levels of tracer uptake in the mouse brain for all 3 radioligands, likely due to their relatively high lipophilicities ( Another group seeking to generate compounds suitable for GHSR imaging in the brain reported a SAR study on fluorinated quinazolinone derivatives with low nanomolar affinities. 94 Substitution at the piperidine nitrogen is known to have an effect on binding to the receptor; therefore, the authors chose a known, high affinity, quinazolinone derivative as a starting point for SAR studies, compound 24. 95 Results from the study revealed that both enantiomers of the original lead candidate, (S)-24 and (R)-24, and a new derivative, (S)-25 had the strongest binding affinities (IC 50 ¼ 2.2 nM, 3.9 nM, and 2.7 nM, respectively).…”
Section: Molecular Imaging Agents Based On Small Moleculesmentioning
confidence: 99%
“…Computational modeling has shown that the binding of these putative imaging agents to GHSR1a is dependent on interaction with hydrophobic binding pockets. 22 Other groups have also developed similar types of tracers that can be labeled with 18 F or 11 C for PET 13,31,32 or 99m Tc for SPECT. 24 Similar to the results from the present study, blocking experiments either did not show much displacement 13 or showed very little displacement, 31 illustrating the difficulty in determining in vivo specificity of tracers that target GHSR1a.…”
Section: Discussionmentioning
confidence: 99%
“…Within a series of derivatives bearing an azaquinazolinone nucleus, one of the scaffolds used in the design of potent GHS-R1a ligands, 92 the fluorinated derivatives ( S )- 52 (IC 50 (affinity) = 2.2 nM), ( R )- 52 (IC 50 (affinity) = 3.9 nM), and 53 (IC 50 (affinity) = 2.7 nM) ( Figure 14 ), endowed with good bioavailability and able to cross the blood-brain barrier (BBB), have recently been identified as suitable compounds for 18 F-labeled PET radiotracers for brain imaging. 93 …”
Section: Medicinal Chemistry Of Ghs-r1a Ligandsmentioning
confidence: 99%